Testing a Mobile Platform for Community Co‐Created Exhibitions. (11th October 2017) - Rogers, Alexandra; Rock, Jenny
Abstract: The benefits of co‐creation between museums and their communities are increasingly acknowledged but challenges remain in creating opportunities for and facilitating enactments of co‐creation. Time, funding and supporting infrastructure are significant hurdles. This study addresses the latter in describing a mobile platform designed for hosting community co‐created exhibitions. It assesses its functionality in two case studies where installations of the platform were hosted by major public museums in New Zealand. Both exhibitions had marine themes, but the co‐creation partners varied from a science education centre and their citizen science collaborators, to an informal group of adults and students engaged in water quality monitoring. Reflective evaluation of the co‐creative process using the platform revealed one of its major benefits to be its professional aesthetic, which allowed work to be presented to a high standard of display, and empowered co‐creators to feel confident in the quality of their work. Further success arose from its physical constraints; a practical scope for exhibitions was demarcated by certain structural limitations and offered relief from what was initially experienced by novice co‐creators as an intimidating amount of freedom within undefined space. Successful elements combined to facilitate key criteria for co‐creation including early and continuous empowerment and co‐ownership between co‐creating parties.